Synthesis of Schiff’s Bases With Simple Synthetic Approach - Dhiraj, Nikam; Rutuja, Nikam; Kalpesh, Shinde; Sunil, Karande (Asian Journal of Pharmaceutical Research and Development, 2020)
A series of Schiff’s bases (3A-G) were synthesized using a simple synthetic approach.0.05 mole of m-nitro aniline and aromatic aldehydes in ethanolic solution was subjected to refluxed for 2 hr to obtain pure products. All the products obtained were having excellent yield in the range of 80-90 % w/w. Products were purified using hot ethanol and reaction was monitored by hexane: ethyl acetate (60:40).